2019
DOI: 10.1002/cncr.32553
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistic parental expectations for cure in poor‐prognosis childhood cancer

Abstract: BackgroundMany parents of children with advanced cancer pursue curative goals when cure is no longer possible. To the authors' knowledge, no pediatric studies to date have prospectively evaluated prognosis communication or influences on decision making in poor‐prognosis childhood cancer.MethodsThe authors conducted a prospective cohort study at 9 pediatric cancer centers that enrolled 95 parents of children with recurrent or refractory, high‐risk neuroblastoma (63% of those who were approached), a condition fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 31 publications
2
62
0
3
Order By: Relevance
“…This is the first study, to our knowledge, to evaluate how adolescents understand their cancer prognosis compared with not just their oncologists at diagnosis but also their parents from diagnosis to one year. Most oncologists reported communicating prognosis to parents and adolescents, similar to some research, 9 but a larger proportion than found in other studies 6,19 . However, oncologists reported they did not provide any prognosis information to at least one parent and 10 adolescents, raising important questions about whether this was driven by the oncologist or family.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This is the first study, to our knowledge, to evaluate how adolescents understand their cancer prognosis compared with not just their oncologists at diagnosis but also their parents from diagnosis to one year. Most oncologists reported communicating prognosis to parents and adolescents, similar to some research, 9 but a larger proportion than found in other studies 6,19 . However, oncologists reported they did not provide any prognosis information to at least one parent and 10 adolescents, raising important questions about whether this was driven by the oncologist or family.…”
Section: Discussionsupporting
confidence: 62%
“…Our results suggest that, similar to parents, 20,21 adolescents fill gaps in their knowledge through alternate sources, with many deriving their understanding of prognosis from parents, other medical staff, personal research, or family or friends. Thus, adolescents frequently desire prognosis information, 9,11,12 but their needs are often unmet, which may influence personal goals of care 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e estar apto a oferecer suporte aos pais e familiares de uma criança com diagnóstico de doença ameaçadora ou limitante da vida (MACK et al, 2005;MASERA et al, 1999;MEERT et al, 2008;MOODY et al, 2011;SAHLER et al, 2000). (BAGATELL et al, 2002;BURKE et al, 2018;MACK et al, 2005MACK et al, , 2019POLES;BOUSSO, 2009 -LANGNER, 2013;MICHELSON et al, 2009;MOODY et al, 2018;SCHIFFMAN et al, 2008;WIDGER et al, 2016).…”
Section: Ensino De Cuidados Paliativos Na Residência Médica Pediátricunclassified